Premenstrual symptoms analysis: severity and correlations across physiological, behavioural, and psychological domains among working women in selected schools at Kalaburagi - J. A., Bemina; Mathias, Thereza (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Working women, especially teachers, face unique challenges in managing health issues that impact their professional lives. Premenstrual symptoms (PMS) significantly affect their physiological, behavioural, and psychological well-being, potentially influencing their classroom performance. This study aimed to assess the severity and correlations of PMS across physiological, behavioural, and psychological domains among 100 working women teachers in Kalaburagi. It also explored associations with socio-demographic variables such as menstrual cycle duration and food cravings. Methods: Data were collected using a cross-sectional correlation research design. Mean scores and standard deviations were calculated for physiological, behavioural, and psychological symptoms. Chi-square tests analysed associations between symptom domains and socio-demographic variables. Correlation analyses assessed relationships between symptom domains. Results: Physiological symptoms scored a mean of 55.60 (SD=2.4, 70% of max. score), behavioural symptoms 45.32 (SD=2.5, 78% of max.), and psychological symptoms 46.90 (SD=2.3, 80% of max.). Overall mean score was 150.15 (SD=2.4, 75% of max.). Positive correlations were found between physiological and psychological symptoms (r=0.810, p<0.001), physiological and behavioural symptoms (r=0.729, p<0.001), and psychological and behavioural symptoms (r=0.627, p<0.001). Conclusions: This study highlights the prevalence of PMS among working women, especially teachers, and their potential impact on professional performance and emotional well-being. The findings underscore the need for effective detection and management strategies to enhance the quality of life and work efficiency of affected women. Targeted interventions and workplace support can improve personal and professional outcomes for women experiencing PMS.